Autoantibodies against apolipoprotein A‐1 after COVID‐19 predict symptoms persistence. (2nd June 2022) - L'Huillier, Arnaud G.; Pagano, Sabrina; Baggio, Stephanie; Meyer, Benjamin; Andrey, Diego O.; Nehme, Mayssam; Guessous, Idris; Eberhardt, Christiane S.; Huttner, Angela; Posfay‐Barbe, Klara M.; Yerly, Sabine; Siegrist, Claire‐Anne; et al.
Abstract: Background: SARS‐CoV‐2 infection triggers different auto‐antibodies, including anti‐apolipoprotein A‐1 IgGs (AAA1), which could be of concern as mediators of persistent symptoms. We determined the kinetics of AAA1 response over after COVID‐19 and the impact of AAA1 on the inflammatory response and symptoms persistence. Methods: All serologies were assessed at one, three, six and twelve months in 193 hospital employees with COVID‐19. ROC curve analyses and logistic regression models (LRM) were used to determine the prognostic accuracy of AAA1 and their association with patient‐reported COVID‐19 symptoms persistence at 12 months. Interferon (IFN)‐α and‐γ production by AAA1‐stimulated human monocyte‐derived macrophages (HMDM) was assessed in vitro. Results: AAA1 seropositivity was 93% at one month and declined to 15% at 12 months after COVID‐19. Persistent symptoms at 12 months were observed in 45.1% of participants, with a predominance of neurological (28.5%), followed by general (15%) and respiratory symptoms (9.3%). Over time, strength of correlations between AAA1 and anti‐SARS‐COV2 serologies decreased, but remained significant. From the 3 rd month on, AAA1 levels predicted persistent respiratory symptoms (area under the curves 0.72‐0.74; p < 0.001), independently of disease severity, age and gender (adjusted odds ratios 4.81–4.94; p = 0.02), while anti‐SARS‐CoV‐2 serologies did not. AAA1 increased IFN‐α production by HMDMs ( p = 0.03), without affecting the IFN‐γ response. Conclusion: COVID‐19 induces a marked though transient AAA1 response, independently predicting one‐year persistence of respiratory symptoms. By increasing IFN‐α response, AAA1 may contribute to persistent symptoms. If and how AAA1 levels assessment could be of use for COVID‐19 risk stratification remains to be determined.